The presence of laugh in Capoeira Angola (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
In this article we analyze the presence of laughter in the roda of Capoeira Angola, using as main fields of analysis the archetype of the trickster and the ethics of trickster style. Laughter is a socio-anthropological phenomenon that establishes the humor and the comic in the absurdities of existence and in the perception of the personal maladjustment or distraction of the individual in relation to social customs. In the popular thinking the archetype of the malandro evokes cunning, wit and ingenuity, and is highly praised among the Angoleiros. The malandragem in Capoeira Angola is discussed here from the corporal dimension, with emphasis on the game, on the joke and especially on the laughter. We analyze the course of trickster style as something that was consolidated in Brazil at the beginning of the 20th century and has greatly influenced the practice of capoeira to the present day.
Keywords: Malandragem; Capoeira Angola; Laughter; Laughable; Game